Thurston syndrome in two Indian female siblings - Samson Samuel; Shrikrishna Parab; Sunil Sharma; Chandan Kumar (Wolters Kluwer Medknow Publications, 2024)
Thurston syndrome (oral-facial-digital syndromes [OFDS] Type V) is characterized by median cleft lip, postaxial polydactyly of hands and feet, and other oral manifestations. It is one of the OFDS described earlier in the literature. It is commonly seen in individuals of Indian origin and has autosomal recessive inheritance. This article presents two Indian female siblings with median upper lip cleft associated with postaxial hexadactyly of both hands. Rarely have such cases been reported by any author. Majority of the previously reported cases are males. This is the first case report of female siblings with Thurston syndrome.